Advances in Sustainable Extraction of Arsenic and Cadmium from Sewage Sludge: Use of Hydrophobic Deep Eutectic Solvent Modified with Magnetic Nanoparticles - Lamarca, Rafaela S. [UNESP]; dos S. Ferreira, Sabrina [UNESP]; Abuçafy, Marina P. [UNESP]; Silva, Leandro S. [UNESP]; Pishro, Khatereh A. [UNESP]; Amaral, Clarice D. B.; Fernandes, Jose O.; Cunha, Sara C.; Franco, Douglas F. [UNESP]; Gonzalez, Mario H. [UNESP] (American Chemical Society (ACS), 2024)
A novel magnetic hydrophobic deep eutectic solvent (MHDES) was synthesized, based on DL-menthol, acetic acid, and pyruvic acid, for subsequent use in the magnetic extraction of inorganic contaminants in sewage sludge samples. First, α-Fe2O3 nanoparticles were synthesized using the coprecipitation method and were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and energy dispersive spectroscopy (EDS) techniques. These nanoparticles were then incorporated into the HDES and this modified material was used as a magnetic extracting agent. The stability of the α-Fe2O3 nanoparticles in HDES medium was confirmed by zeta potential measurements. The developed MHDES was tested in the extraction of arsenic (As) and cadmium (Cd) from certified samples of sewage sludge, obtaining average recovery values of 106% and 93.2% for As and Cd, respectively. The limit of detection (LOD) and limit of quantification (LOQ) values for As were 0.160 and 0.530 μg L-1, respectively, while the corresponding values for Cd were 0.280 and 0.940 μg L-1, respectively. The elemental compositions of real sewage sludge samples were evaluated by X-ray photoelectron spectroscopy (XPS). The MHDES was used to extract two samples of real sewage sludge, obtaining values of 4.89 ± 0.2 μg g-1 (sample A) and 3.80 ± 0.1 μg g-1 (sample B) for arsenic, and 2.11 ± 0.07 μg g-1 (sample A) and 2.10 ± 0.07 μg g-1 (sample B) for cadmium. The extraction process was evaluated using AGREE software, obtaining a score of 0.73 (out of a total of 1.0). The proposed method using vortex and MHDES provided effective extraction of As and Cd from sewage sludge, with high potential for application to other matrices.
Keywords: green metrics; ICP-MS; magnetic hydrophobic deep eutectic solvent (MHDES); sample preparation